Comparative Study Between Lateral Laminectomy And Crushing Technique In Management Of Patients Who Underwent Septoplasty With Concha Bullosa (Journal of Pharmaceutical Negative Results, 2023)
Background: Among of the most frequent anatomical alterations of the lateral nasal wall is concha bullosa (CB), which is pneumatisation of the concha. Aim: The main objective of the study was to compare between the two regularly used surgical procedures (lateral laminectomy and crushing technique) of lateral excision and crushing for Concha Bullosa (CB). Methods: NOSE score was assessed for individuals who had been characterized with DNS and CB employing endoscopy and computerised tomography. All participants received septoplasty, and individuals were divided into two groups based on the surgical technique used to treat CB. Artery forcepswere used in group I to crush the middle turbinate, while group II underwent lateral CB resection. At one month after surgery, postoperatively NOSE ratings were performed, and a comparison was made. Results: Both surgical techniques were quite successful in treating CB. Once comparing to preoperatively readings, the NOSE scores of all participants significantly improved. There was no statistical significant difference between the two surgical techniques. Conclusion: The anatomy of the nose and paranasal sinus frequently exhibits CB. It commonly coexists with DNS and, if over pneumatized, can result in sinus issues. Such circumstances call for surgical treatment. Although both lateral resection and the crushing of MT are frequently used procedures, the crushing method has the benefit of protecting the mucosa and causing fewer postoperatively problems.